Creative Thinking in Prospective Mathematics Teachers: Flexibility in Solving Systems of Linear Equation - Maharani, Hevy Risqi; Basir, Mochamad Abdul; Ningrum, Niken Lusia (Jurnal Pendidikan Progresif, 2024)
Creative Thinking in Prospective Mathematics Teachers: Flexibility in Solving Systems of Linear Equations. Objectives: The main aim of this research is to determine the flexibility of prospective mathematics teachers in solving systems of linear equations. Apart from that, this research also aims to find factors that are taken into consideration by prospective mathematics teachers in determining the method for solving systems of linear equations. Methods: Data collection techniques are carried out through tests. The test is used to determine the flexibility or number of methods used by prospective mathematics teachers in solving systems of linear equations. Qualitative descriptive methodology and interviews with prospective mathematics teachers were used in this research to interpret the results and analyze the factors considered by prospective mathematics teachers in choosing the method used to solve systems of linear equations. Findings:The results of this research reveal that prospective mathematics teachers have 6 methods that can be used to solve systems of linear equations. Conclusion: The factors taken into consideration by teachers in determining the chosen method are based on three numerical factors, namely the number of variables to be searched for, the number of operations to be used and the number of steps to be carried out in solving a system of linear equations. Keywords: creative thinking, flexibility, mathematics. DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202459